Pengaruh Penerapan Bahan Ajar E-Book Terhadap Hasil Belajar Peserta Didik Kelas VIII pada Materi Sistem Pernapasan Manusia - Sainab, Sainab (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to determine the effect of using e-book teaching materials on the learning outcomes of class VIII students of SMP Negeri Limboro. The approach used in this study is a quantitative approach with a quasi-experimental research design in the form of a nonequivalent control group design. The sample in this study were students in class VIII A and class VIII B, totaling 58 students using the sampling technique, namely saturated sampling. The instrument used in this study is a test. The data analysis technique used in this study was the t-test, the collected data was processed and analyzed using the N-Gain test and the independent sample t-test through SPSS 24. The results of this study indicate that there is aneffect of using e-book teaching materials on results student learning, this is evidenced bystatistical analysis which states that the tcount > ttable (3.749 > 2.003) and a significance value of 0.000 <0.05 then H0 is rejected and H1 is accepted.